УЧАСТЬ МОЛДАВІЇ І ВАЛАХІЇ У ХОТИНСЬКІЙ ВІЙНІ 1621 РОКУ - Chuchko, Mykhaylo; Чучко, Михайло Костянтинович (Чернівці, Чернівецький національний університет, 2022)
The article is devoted to the little-studied problem of participation in the Khotyn War of 1621, which took place between the Commonwealth and the Ottoman Empire, the principalities of Moldavia and Wallachia, dependent on the Ottoman Porte. The author notes that during this Polish Ottoman military conflict, the decisive battle of which took place near Khotyn, the troops of the rulers of the Danube principalities participated in hostilities. and they themselves played an important mediating role in the peace negotiations between the Ottoman and Polish sides. On the march to the theater of operations, the army of Sultan Osman II was joined by 6-7 thousand soldiers of the Wallachian governor Radu Mihnea and 5 thousand soldiers of the Moldavian governor Alexandru Iliaș, who had previously fled from Iași to Roman. And at first, only Myron Barnovsky managed to organize resistance to the advanced Polish detachments that arrived in the vicinity of Khotyn, who later, together with detachments of the Khan Temir Budzhak Tatars, also continued to attack Polish foragers. At the end of August, on the way to Khotyn, Osman II removed from power the Moldavian governor Alexandru Iliaș, who failed to prevent the devastating raids by the country of Polish and Cossack detachments that robbed the population. Temporarily, the duties of the prince of Moldavia were entrusted to the voivode of Wallachia, Radu Mihnea. On the field of the Battle of Khotyn, the troops of Radu Mihnea - the Vlachs and the Moldavians were located between the Aleppo and Damasc units. By order of the Sultan, the Moldavians built a bridge across the Dniester for the Ottomans, and the protection of this bridge was entrusted to the Vlachs. Detachments of the Danubian principalities, together with other units, including the Tatars, also participated in the battles near Khotyn, in particular, they took part in the assaults of the Polish positions by the troops of the Sultan on September 6 and 28. In parallel with the military clashes, negotiations were underway to resolve the conflict, which began with the mediation efforts of the Moldavian prince Alexander Ilias and the Wallachian governor Radu Mihnea almost immediately after the start of the war. Later, the voivode of Wallachia Radu Mihnea acted as an intermediary in the negotiations between the Ottomans and the Polish side, who, through the Cretan Constantine Batista Vevelli, played an important mediating role in their conduct. These negotiations culminated in the signing of the Polish-Ottoman peace agreement on October 9, 1621, under which the Khotyn castle was returned to the Moldavian principality.
PARTICIPATION OF MOLDOVA AND WALLAHIA IN THE KHOTYN WAR OF 1621
Keywords: Khotyn War, Ottoman Empire, Rzeczpospolita, Moldavia, Wallachia, Khotyn.